THE EFFECTIVENESS OF USING THE TEAM BASED LEARNING (TBL) LEARNING MODEL TO INCREASE INTEREST IN LEARNING CRITICAL THINKING SKILLSAND ECONOMIC LEARNING ACHIEVEMENT OF STUDENTS AT SMA NEGERI 1 AMARASI, KUPANG REGENCY - Ani Julistya Kristine Moruk Tuka; Ali Muhson (International Journal of Teaching and Learning, 2024)
This study discusses the Effectiveness of the Team Based Learning Learning Model to Increase Learning Interest, Critical Thinking Ability and Student Achievement at SMA Negeri 1 Amarasi, Kupang Regency. This study aims to determine the effectiveness of using the Team Based Learning (TBL) learning model to increase learning interest, critical thinking skills and student achievement at SMA Negeri 1 Amarasi and the effect of using the Team Based Learning (TBL) learning model to increase learning interest, critical thinking skills and student achievement of SMA Negeri 1 Amarasi. The results of the N-gain data analysis and the Manova test show that 1) the Team Based Learning learning model is quite effective in increasing student interest in SMA Negeri 1 Amarasi. 2) the learning model of Team Based Learning is effective enough to improve the critical thinking skills of SMA Negeri 1 Amarasi students. 3) the learning model of Team Based Learning is quite effective in increasing student achievement in SMA Negeri 1 Amarasi. 4) there is an effect of using the Team Based Learning learning model on increasing interest in learning, critical thinking skills and student achievement of SMA Negeri 1 Amarasi with a significance value of 0.000.